2018
DOI: 10.18632/oncotarget.26014
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma in the setting of prior lower grade gliomas - insights from SEER database

Abstract: IntroductionSecondary glioblastomas (GBs) constitute a small subset of all GBs and tend to arise after a lower grade glioma. Though knowledge regarding this subset has gained traction in recent years, its definition continues to evolve, complicating its clinical management. Investigation of epidemiology and survival patterns may help provide needed insights.ResultsThe age at GB diagnosis is significantly lower (46.22 vs 60.25 years) for group B. The distribution among type of GB (glioblastoma, giant cell gliob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Surgery, radiation therapy, chemotherapy or a combined approach is used as a standard treatment regimen for LGG. 32 Its treatment is crucial based on the fact that it can evolve into secondary GBM which carries a notorious therapy‐resistant nature 33 ; hence, the treatment success is crucial for LGGs. In order to understand the possible contribution of TXNDC5 in this process, we investigated TXNDC5 levels in LGG patients having primary tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Surgery, radiation therapy, chemotherapy or a combined approach is used as a standard treatment regimen for LGG. 32 Its treatment is crucial based on the fact that it can evolve into secondary GBM which carries a notorious therapy‐resistant nature 33 ; hence, the treatment success is crucial for LGGs. In order to understand the possible contribution of TXNDC5 in this process, we investigated TXNDC5 levels in LGG patients having primary tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have evaluated glioma by including either LGG as a broad category or comparing LGG with HGG. 1 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 Several studies evaluated the epidemiology of gliomas and demonstrated increased likelihood in Caucasians, older, or male patients, patients with prior smoking history, women with prior breast cancer treatment, and insured patients. 13 14 15 16 19 Plascak et al evaluated 24,230 glioma patients using the SEER database between 2000 and 2006; they showed a greater incidence of gliomas in countries with higher socioeconomic status, which suggested unequal distribution of diagnostic resources.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have suggested that White race, younger age, more recent diagnosis, lower WHO grade or histology, marital status, better socioeconomic status, EOR, radiotherapy, radiochemotherapy, treatment at high-volume facilities, and tumor size positively impact patient prognosis. 1,4,16,17,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Missios et al evaluated 21,384 cases of glioma between 2005 and 2011 using the National Inpatient Sample (NIS) database and showed that perioperative complications were increased by greater age, coagulopathy, coronary artery disease, congestive heart failure, and smoking history. 37 Although these studies have had an impact by identifying consistent risk and prognostic factors, they are limited by aggregating glioma types, mostly as a limitation of lacking molecular data in nearly all multicenter databases.…”
Section: Low Grade Gliomamentioning
confidence: 99%